Atmospheric Correction of DSCOVR EPIC: Version 2 MAIAC Algorithm - Lyapustin, A.; Wang, Y.; Go, S.; Choi, M.; Korkin, S.; Huang, D.; Knyazikhin, Y.; Blank, K.; Marshak, A. (Frontiers in Remote Sensing, 2021)
The Earth Polychromatic Imaging Camera (EPIC) onboard the Deep Space Climate Observatory (DSCOVR) provides multispectral images of the sunlit disk of Earth since 2015 from the L1 orbit, approximately 1.5 million km from Earth toward the Sun. The NASA’s Multi-Angle Implementation of Atmospheric Correction (MAIAC) algorithm has been adapted for DSCOVR/EPIC data providing operational processing since 2018. Here, we describe the latest version 2 (v2) MAIAC EPIC algorithm over land that features improved aerosol retrieval with updated regional aerosol models and new atmospheric correction scheme based on the ancillary bidirectional reflectance distribution function (BRDF) model of the Earth from MAIAC MODIS. The global validation of MAIAC EPIC aerosol optical depth (AOD) with AERONET measurements shows a significant improvement over v1 and the mean bias error MBE=0.046, RMSE=0.159, and R=0.77. Over 66.7% of EPIC AOD retrievals agree with the AERONET AOD to within ±(0.1+0.1AOD). We also analyze the role of surface anisotropy, particularly important for the backscattering view geometry of EPIC, on the result of atmospheric correction. The retrieved BRDF-based bidirectional reflectance factors (BRF) are found higher than the Lambertian reflectance by 8-15% at 443nm and 1-2% at 780nm for EPIC observations near the local noon. Due to higher uncertainties, the atmospheric correction at UV wavelengths of 340, 388nm is currently performed using a Lambertian approximation.